Edgar Valcárcel - Invención (1966) - Ledesma, Yemit (2024)
During his stay as a visiting composer at the Columbia – Princeton Electronic Music Center (New York, 1967), a young Edgar Valcárcel, around 34 years old, created his first work for electronic sounds called Invención. The work immerses us in a variety of electronic sound waves, combined with filtered noise that, making use of traditional electroacoustic techniques (cutting, splicing magnetic tape and creating loops) results in an introspective and disturbing sound atmosphere.